MicroRNA-182 promotes leptomeningeal spread of non-Sonic Hedgehog-medulloblastoma - Bai, Alfa H. C.; Milde, Till; Remke, Marc; Rolli, Claudio Gavino; Hielscher, Thomas; Kool, Marcel; Jugold, Manfred; Bazhin, Alexandr V.; Eichmüller, Stefan B.; Kulozik, Andreas; Pscherer, Armin; Benner, Axel; et al. (Acta neuropathologica, 2012)
The contribution of microRNAs to the initiation, progression, and metastasis of medulloblastoma (MB) remains poorly understood. Metastatic dissemination at diagnosis is present in about 30% of MB patients, and is associated with a dismal prognosis. Using microRNA expression profiling, we demonstrate that the retinal miR-183-96-182 cluster on chromosome 7q32 is highly overexpressed in non-sonic hedgehog MBs (non-SHH-MBs). Expression of miR-182 and miR-183 is associated with cerebellar midline localization, and miR-182 is significantly overexpressed in metastatic MB as compared to non-metastatic tumors. Overexpression of miR-182 in non-SHH-MB increases and knockdown of miR-182 decreases cell migration in vitro. Xenografts overexpressing miR-182 invaded adjacent normal tissue and spread to the leptomeninges, phenotypically reminiscent of clinically highly aggressive large cell anaplastic MB. Hence, our study provides strong in vitro and in vivo evidence that miR-182 contributes to leptomeningeal metastatic dissemination in non-SHH-MB. We therefore reason that targeted inhibition of miR-182 may prevent leptomeningeal spread in patients with non-SHH-MB.
First online: 02 December 2011
Gesehen am 18.09.2018